Quantification of aerobic determinants of performance in post-pubertal adolescent middle-distance runners - Blagrove, R. C.; Howatson, G.; Pedlar, C. R.; Hayes, P. R. (European Journal of Applied Physiology, 2019)
Purpose: The use of oxygen cost (Oaero) parameters to predict endurance performance has recently been criticized. Instead, it is suggested that aerobic energy cost (Eaero) provides greater validity; however, a comparison of these quantification methods has not previously been made. Methods: Fifty-six male (n = 34) and female (n = 22) competitive adolescent (17 ± 1 years) middle-distance runners participated in a sub-maximal and maximal incremental treadmill test. Running economy (RE) was measured at the speed corresponding to lactate turnpoint, and the three speeds prior. Maximal oxygen uptake (VO2max), speed at VO2max and fraction of VO2max utilized across a range of intensities, and speeds from 0.8, 1.5 and 3 km races were also quantified. RE and fractional utilization were calculated in units of Oaero and Eaero. Results: Multiple linear regression models demonstrated no discernible difference in the predictive capability of RE, fractional utilization and VO2max when expressed as Oaero or Eaero in both sexes. When plotted as a function of running speed, Oaero displayed a stepwise decrease (F = 11.59, p < 0.001) whereas Eaero exhibited a curvilinear response (F = 4.74, p = 0.015). Differences were also evident in the slopes plotted for %VO2max and %Eaeromax against running speed (F = 5.38, p = 0.021). Conclusions: Quantifying aerobic determinants of performance in units of Eaero provides no greater validity compared to Oaero-based measurement. Although both Eaero and Oaero are sensitive to changes in speed, Eaero provides the more valid reflection of the underlying metabolic cost of running. Physiologists should also be aware of the potential differences between expression of aerobic running intensity based upon %VO2max compared to %Eaeromax.